PERANAN STRUKTUR KEPEMILIKAN, DEBT COVENANT, DAN GROWTH OPPORTUNITIES TERHADAP KONSERVATISME AKUNTANSI - HARAHAP, SHERLY NOVIANA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Conservatism is an important convention of financial statements in accounting. Conventions such as conservatism into consideration in accounting for financial statements for the company's activities completed by the uncertainty. Conservatism is an accounting principle that if implemented will result in these figures tend to be low income and assets, and the figures tend to be high cost and debt. As a result, reported earnings tend to be too low (understatement). The trend was due to slow recognition of the principle of conservatism and accelerate the recognition of fee income. The factors that play a role in determining accounting conservatism is Ownership Structure, Debt Covenant, and Growth Opportunities. Ownership structure is very important in determining the value of the company and is one of the internal factors that determine the progress of the company. Debt covenant is an agreement to protect the lender from the actions of managers to the interests of creditors. Growth opportunities is the opportunity for companies to invest on things that benefit. Growth is an element that occurs in a cycle of the company.